Characterising the level of crashworthiness for impacts on hard ground and water surfaces for a metallic helicopter under floor structure: What lessons can be learned? - Hughes, Kevin (Cranfield University, 2008)
Helicopters are seen by the petroleum industry as the only viable way of transportation between on and offshore platforms. At present, there exists no certification requirement to ensure a high level of survivability in the event of a water impact. Within the literature, there exists a body of information related to the post crash analysis of accident data, which supports the finding that a conventional metallic under floor design performs poorly during a water impact, in relation to the transmission of water pressure and the absorption of energy. In order to characterise this behaviour, this paper concerns the crashworthiness of helicopters to two extremes in loading, namely hard ground and water surfaces, for an impact speed of 8ms-1, for a simple box-beam construction common to metallic helicopters. The experimental findings were used to validate finite element simulations, with a view for assessing the level of crashworthiness currently offered, together with identifying potential design improvements. To improve the level of crashworthiness, careful redesign of frames, joints and skin is required, together with developing a passive next generation floor that can cater for both hard surface and water impacts, by being able to degrade its localised strength, depending upon the type of surface encountered.